ANALISIS BIBLIOMETRIK BUAH BIT (Beta vulgaris L.) UNTUK ANTIOKSIDAN - Zenita, Risma; Yuniarti, Elsa (Universitas Cokroaminoto Palopo, 2025)
Beetroot or known as Beta vulgaris L. is a plant from the Amaranthaceae family. One source of natural antioxidants for this plant is the leaves, fruit and tubers. The compounds in beet plants contain many free radical inhibitor molecules, such as active compounds in the form of flavonoids and tannins as well as nitrogen compounds in the form of betalains and terpenoids (carotenoids). Antioxidants can also help prevent various chronic diseases such as heart disease, cancer and diabetes. Apart from that, beets can also help metabolism in our body. The aim of this research is to gain insight into the latest research development trends regarding the antioxidant potential of beets. This research uses quantitative methods with Bibliometric analysis of national and international publication data sourced from the Scopus database. In the overlay visualization display section, a lot of research has been carried out on Beta vulgaris. Research on Beta vulgaris was mostly carried out in 2022 with 3 clusters and 21 keywords. The most researched keyword density is Beta vulgaris, antioxidant, and metabolism which are marked in yellow. This shows that there are still few researchers researching this topic so that the opportunities for further research regarding Beta vulgaris are very broad.